Penggunaan Berbagai Metode Pembelajaran untuk Meningkatkan Keterampilan Berbicara Bahasa Indonesia - Fitri Handayani; Desty Endrawati Subroto; Vivi Nurkhofifah; Nurhalifah Nurhalifah; Muchamad Rizky Akbar (Politeknik Kampar, 2025)
Education is a process that takes place continuously and without end, aiming to change human attitudes and behavior so as to produce quality individuals. Language acts as a means of communication used to convey thoughts and feelings through symbols or signs. The ability to speak allows someone to convey ideas or messages orally clearly to others. In a formal context, the use of good and correct Indonesian is very important to convey information accurately. The ability to speak Indonesian has a strategic role because it is the unifying language and is widely used in education. However, in several regions such as Aceh, Madura, West Kalimantan, and Papua, the ability to speak Indonesian is still relatively low. Therefore, this study aims to examine learning methods that can improve students' speaking ability in Indonesian. This study uses a qualitative descriptive approach. Based on the literature review, several effective learning methods were found, such as the carousel method, discussion, assignments, utilization of the environment as a learning resource, and audio-visual methods. The results of the study showed that these methods made a significant contribution to improving students' Indonesian speaking skills. In addition, technology has also proven effective in supporting the improvement of good and correct Indonesian speaking skills.